Refractory Pulmonary Interstitial Emphysema in Extreme Premature Newborn - Mahmoud Ali; Lea Mallett; Greg Miller (Thieme Medical Publishers, Inc., 2021)
Pulmonary interstitial emphysema (PIE) occurs when air leaks into the pulmonary interstitium due to overdistension of distal airways, it occurs mainly in neonates with respiratory distress syndrome who need positive pressure ventilation but has also been reported in spontaneously breathing infants. Herein, we report on an extremely low birth weight infant with severe persistent PIE, while on invasive mechanical ventilation (high-frequency oscillatory ventilation, high-frequency jet ventilation, and neurally adjust ventilator assist) managed successfully with 2 weeks of selective right lung ventilation after failure of more conservative measures, including shorter periods of right mainstem intubation, before the prolonged trial that was successful.